Additive manufacturing in edible product supply chain: a sustainable perspective - Li, Wenqi; Ekren, Banu Y.; Aktas, Emel (Springer, 2025)
As the quest for healthier lifestyles intensifies, there is a growing demand for customized nutritional options, challenging the traditional food supply chain with its perishable goods and unpredictable demand patterns. This paper explores the potential of additive manufacturing, or 3D printing, as an innovative solution to these challenges. We present a conceptual framework to assess the impact of AM on the supply chain of edible products, including food and medicine, through the lens of sustainability—encompassing environmental, social, and economic perspectives. Our systematic literature review identifies five key strategies through which AM can enhance supply chain sustainability: distributed localized manufacturing, in-house production, delayed production, mass customization, and on-demand production. This research contributes valuable insights for industry practitioners and policymakers, guiding them toward exploiting AM's potential to revolutionize the sustainable supply chain management of edible products. Our findings highlight the transformative capabilities of AM and set the stage for future research directions in the nexus of additive manufacturing and sustainable supply chain practices.
Keywords: 3509 Transportation, Logistics and Supply Chains; 4014 Manufacturing Engineering; 40 Engineering; 35 Commerce, Management, Tourism and Services; Generic health relevance; 12 Responsible Consumption and Production; 9 Industry, Innovation and Infrastructure; 2 Zero Hunger; Edible product; Supply chain; Sustainability; Additive manufacturing